Dear participants of the Congress, scholars, and distinguished guests! (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
On behalf of the Cabinet of Ministers of the Kyrgyz Republic, as well as the Chairman of the Organizing Committee of the World Festival of Traditional Culture and Music «Ruh Sanat,» I sincerely congratulate you on the publication of the materials of the International Congress «Traditional Culture and Art: Issues of Preservation and Development» in the form of a special edition of the scientific journal «Proceedings of the National Academy of Sciences of the Kyrgyz Republic»!
Keywords: -